Rapid removal of thallium from water by a new magnetic nano-composite using graphene oxide for efficient separation. (July 2021) - Li, Liangzhong; Liu, Chang; Ma, Ruixue; Yu, Yunjiang; Chang, Zhaofeng; Zhang, Xiaohui; Yang, Chengyu; Chen, Da; Yu, Yang; Li, Wei; Liu, Yongdi
Abstract: Thallium contamination has raised global concern due to its high toxicity and treatment difficulties. In this study, the magnetic adsorbent rGO-Fe3 O4 @TiO2 was synthesized for the effective removal of thallium(I) from water. The stable magnetism of the adsorbent before and after the adsorption ensured the facile magnetic separation from treated streams. The abundant hydroxyl groups on the surface of nano-sized TiO2 particles served as adsorptive sites for the Tl(I) ions. The adsorbent performed a fast adsorption rate of Tl(I), achieving approximately 50% of ultimate adsorbed amount within the initial 10 min at near neutral condition (pH 7.0). Tl(I) removal was significantly enhanced by increasing solution pH value due to the electrostatic attraction between Tl(I) ions and the adsorbent surface. Isotherm study showed that the adsorption process was favorable, with the maximum adsorption capacity of 141.8 mg g −1 . The presence of co-existing cations might interfere and compete with the adsorption sites of Tl(I) ions. The prepared magnetically responsive adsorbent with good regeneration ability could be used as a competitive alternative to address the sudden thallium pollution incidents considering its rapid rate and high efficiency for Tl(I) adsorption and removal from aqueous systems. Graphical abstract: Image 1 Highlights: Stable magnetism of sorbent ensures efficient magnetic separation after treatment. 50% of ultimate adsorbed amount can be achieved within the first 10 min at pH 7.0. q max of sorbent occupies competitive position compared to other magnetic sorbents. Tl(I) ions are adsorbed on sorbent surface via the formation of Ti–O–Tl linkages.